HUBUNGAN TINGKAT PENGETAHUAN LANSIA TERHADAP PENATALAKSANAAN HIPERTENSI - Anitha, Anitha (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2021)
Hypertension is commonly occurred by a number of elderly and adversely affects vital organs such as the heart and kidneys so that it can cause death. Deaths by hypertension can be prevented and treated by treating hypertension. Handling of hypertension is pharmacology handling and non-pharmacology handling. The purpose of this study was to determine the relationship of knowledge level with the handling of hypertension in the elderly in RT 10 Kelurahan Rawa Buaya. The research design used was cross-sectional design and data were collected using a questionnaire. The sample amounted to 48 respondents and was taken by random sampling. Result of research based on chi-square statistical test, there is a significant correlation between knowledge level with hypertension handling in the elderly (p-value = 0,002). The conclusion of the research shows that there is a correlation between the level of knowledge with the handling of hypertension in the elderly in the RT 10 Kelurahan Rawa Buaya. Suggestions for researchers further expected this research can be a reference and the beginning for much more research about the factors that affect the handling of hypertension in elderlyKeywords: Knowledge, Seniors, Hypertension Handling